Guest

prove that in a triangle ABC summation(sinAsin(B-C))=0

prove that in a triangle ABC summation(sinAsin(B-C))=0

Grade:

2 Answers

Karthik Pasupulatei
38 Points
6 years ago
first write sin2A then 2SINA.COSA then write 2SINA.COS(90-B-C) THEN U WRITE 2SINA SIN(B-C)
Lab Bhattacharjee
121 Points
6 years ago
B+C=\pi-A\implies\sin(B+C)=\cdots=\sin A \\ \sin A\cdot\sin(B-C)=\sin(B+C)\sin(B-C)=\sin^2B-\sin^2C

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free